Pengaruh latihan incline bound dan decline hop terhadap power otot tungkai atlet bola voli club sambinae kota bima tahun 2022 - Nursakinah; Arif Yanuar Musrifin; Fitri Anggraini Haryanto; Subakti (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
The Sambinae volleyball club is one of the volleyball coaching associations in the city of Bima, where recently the volleyball sports achievement has decreased so we need to conduct an evaluation, the most basic technique is related to the physical problems of athletes, especially leg muscle power where the role of leg muscle power is it is very important, apart from doing the jump smash, it is also used to block the opponent’s attack from above the net. The purpose of this study was to determine the effect of Incline Bound and Decline Hop exercises on leg muscle power of vellyball athletes at Sambinae Club Bima City in 2022”. The sample used was 12 people. The data collection method uses the action test method as the main method, namely by conducting an initial test. Before doing exercise using Incline Bound and Decline Hop (pre-test) and after exercise (post-test). Research instrument test to measure leg muscle power with vertical jumpt test. Meanwhile, the data analysis method using statistical analysis with t-test formula. The results of data analysis where the treatment using Incline Bound has a significant effect where t-count is greater than t-tabel (2,254 ˃ 2,015) so based on the above analysis ho is rejected and ha is accepte. Meanwhile data lysis where treatment using Decline Hop has a significant effect where t-count is greater than t-tabel (2,264 ˃ 2,015) so based on the above analysis ho is rejected and ha is accepted.